Alterations in insulin receptor signalling in the rat epitrochlearis muscle upon cessation of voluntary exercise - Kump, David S (Blackwell Science Inc, 2005)
The major purpose of this study was to elucidate mechanisms by which decreasing enhanced physical activity induces decreased insulin sensitivity in skeletal muscle. Rats with access to voluntary running wheels for 3 weeks had their wheels locked for 5 h (WL5), 29 h (WL29), or 53 h (WL53); a separate group of rats never had wheel access (sedentary, SED). Relative to WL5, submaximal insulin-stimulated 2-deoxyglucose uptake into the epitrochlearis muscle was lower in WL53 and SED. Insulin binding, insulin receptor β-subunit (IRβ) protein level, submaximal insulin-stimulated IRβ tyrosine phosphorylation, and glucose transporter-4 protein level were each lower in both WL53 and SED than in WL5 and WL29. Akt/protein kinase B Ser(473) phosphorylation was lower in WL53 and SED than in WL5. Protein levels of protein tyrosine phosphatase-1B, Src homology phosphatase-2, and protein kinase C-Θ did not vary among groups. The amount of protein tyrosine phosphatase-1B, Src homology phosphatase-2, and protein kinase C-Θ associated with IRβ in insulin-stimulated muscle also did not differ among the four groups. The mean of SED and WL53 had a significantly higher IRβ-associated protein tyrosine phosphatase-1B than the mean of WL5 and WL29. The enclosure of multiple changes (decreases in insulin binding, IRβ protein, IRβ tyrosine phosphorylation, and glucose transporter-4 protein) in the epitrochlearis muscle within the 29th to 53rd hour after cessation of voluntary wheel running raises the possibility that a single regulatory event could be responsible for the coordinated decrease.